Dermatological Pathology in a Homeless Population - Fernandes, Bárbara Cristina (2019)
Introduction: The homeless population has a higher risk for skin diseases. Life on the streets, associated with poor hygiene and eating habits, higher prevalence of addictive behaviors and psychiatric comorbidities make this population more susceptible to dermatosis. Our objective was to perform a dermatological examination, as complete as possible, of the homeless people accompanied by the Project of Intervention within the homeless population of Coimbra. After diagnosing a dermatosis, the adequate treatment is bought and started; whenever required, further management and follow-up are conducted in consultations of Dermatology. Furthermore, awareness and education for the importance of skin care is implemented for all the people observed. Material and Methods: The study was carried out between February 24, 2018, and January 19, 2019, evaluating individuals voluntarily enrolled who were living in temporary residence for homeless people in Coimbra (CAIS, Farol, Casa Abrigo Padre Américo) and supported by the team of Rua Reduz, by the Centro Municipal de Inserção Social and by the associations Sol Nascente and VHIDA +. In addition to the dermatological history and examination, demographic data, weight, height and medical history (including, mental illness, addictive behaviors and co-existence of HIV infection) were collected. Some participants also completed the DLQI questionnaire. Results: The 111 individuals evaluated had a mean age of 47.0 years, 83.8% were male, mostly single (60.7%) or divorced (29.9%); the Portuguese nationality was more prevalent (86.5 %). Globally, they had a lower level of education (63.9% with a level of education up to the 6th grade). The more prevalent skin diseases were eczema, tinea pedis, onychomycosis, seborrheic dermatitis and callosities. Among the 54 homeless individuals who completed the Dermatology Life Quality Index (DLQI) questionnaire, the majority (85.1%) reported little or no effect on quality of life. Conclusion: Most dermatoses were of mild severity and easy management, certainly due to the relatively good and healthy food and adequate hygiene care that we could observe in the homeless shelters, together with the very good connection among these units and the primary health care services. Our data were obtained from a homeless population living in a temporary residence and, thereby, they could not be representative of the dermatoses that could be found in the street homeless population, where poor hygiene and eating habits may lead to a higher prevalence and severity of skin diseases.